Formation and elimination mechanisms of prior particle boundaries in a new powder metallurgy superalloy - Qiu-Mei Yang; Y.C. Lin; Wei-Wei Zhao; Guan Liu; Zi-Jian Chen; Jun-Cheng Zhu; Ming-Song Chen; Yu-Liang Qiu (Journal of Materials Research and Technology, 2023)
The formation of prior particle boundaries (PPBs) in a new powder metallurgy superalloy during hot isostatic pressing (HIP) is investigated. Also, the impact of subsequent hot deformation on the elimination of PPBs is systematically studied. The PPBs involves large γ′ phases, carbides (MC and M6C) and oxides (Al2O3, SiO2 and ZrO2). The reactions among the superficial oxides, the adsorbed C and O elements on the particle surface and internally-migrated alloying elements are the dominant reasons for the formation of PPBs during HIP. Besides, the existence of surface tension and surface energy induces the carbon segregation, as well as the formation of PPBs. Thus, the density of PPBs decreases when the spacing between powders is shrunk by a rapid deformation. In hot forming process, the PPBs can be efficiently eliminated via raising deformation temperature/true strain or reducing strain rate. The interactions between dislocations and PPBs, as well as the occurrence of dynamic recrystallization (DRX) induced by the strain/orientation gradient, lead to the elimination of PPBs. The thermodynamic stability of carbides declines with the raised temperature. It indicates that the dissolution of carbides and the elimination of PPBs can be accelerated via raising the deformation temperature. The breakage or deformation behavior of PPBs during hot extrusion is investigated by numerical simulation. The deformation degree of PPBs increases with the raised extrusion ratio. The above important findings are useful for developing hot extrusion processing to effectively eliminate PPBs.